Organization as strategy: Restructuring production in the film industry - Robins, James Arthur (Strategic Management Journal, 1993)
Few changes in the structure of firms have attracted as much attention during the last decade as the movement away from integrated production and toward cooperative relations among independent organizations. Despite recent emphasis on these strategies of 'disaggregation' and 'network' organization, little quantitative research exists on the impact of this type of reorganization on economic performance—at least in part due to the difficulty of obtaining appropriate data. The economic impact of disaggregation is examined in this paper using data on film production in the period after World War II.